Simulações para a análise de mudanças climáticas e seu efeito sobre os recursos hídricos da bacia hidrográfica do rio Palma (TO) - Ribeiro, Camila Lúcia Cardoso (2021)
In a scenario of increasing demand for water in agriculture, industry and for energy generation, influenced by climate change, it is important to use tools to assist in the management of water resources. Hydrological and climatic models, as well as the system dynamics methodology, can simulate real situations, such as the processes that occur in a water basin. The objective of this study was to evaluate the water resources sustainability in the Palma River basin, and to simulate the impacts of climate change on the irrigation demand of the main agricultural crops in the basin. For this, a system dynamics model was created in the STELLA software, representing water supply and demand, as well as the main components and relationships among them that influence the water stock in the basin. For water supply, future runoff data generated in the SWAT model were used, considering climate projections from the Eta-CPTEC/MIROC5 and Eta-CPTEC/HadGEM2-ES models, and the RCPs 4.5 and 8.5 emission scenarios. With regard to water demands, data from IBGE censuses and projections were used for population and livestock growth rates, and data from ABIMAQ for irrigated agriculture. Irrigation demand was simulated in AquaCrop, using potential evapotranspiration data also generated in SWAT. The planning horizon for the STELLA simulations was from 2007 to 2099, with a monthly time unit. The scenarios evaluated were climate change and growth in irrigated area. To evaluate the sustainability of water resources in the basin the Sustainability Index (SI) was used. As for the results, in AquaCrop, the scenarios that considered the climate projections of the Eta/HadGEM2-ES model for RCP 8.5, were the ones that presented the highest average irrigation demand values. All the scenarios evaluated showed an upward trend in annual irrigation demand. In STELLA, when considering the Eta/HadGEM2-ES model for the 8.5 emission scenario, there was a higher number of unsustainable months, which shows that this model can predict larger hydrological impacts. A trend of decreasing SI and increasing unsustainable months was observed for most scenarios. Thus, climate change and the consequent increase in water demand for crop irrigation, may contribute to future problems in water availability. These results can assist in the management of water resources, in order to prevent the situation in the basin from becoming unsustainable and the use of its resources can continue without affecting its ecosystem.